Sequencing analysis reveals a unique gene organization in the gyrB region of Mycoplasma hominis. - Ladefoged, S A (1994)
The homolog of the gyrB gene, which has been reported to be present in the vicinity of the initiation site of replication in bacteria, was mapped on the Mycoplasma hominis genome, and the region was subsequently sequenced. Five open reading frames were identified flanking the gyrB gene, one of which showed similarity to that which encodes the LicA protein of Haemophilus influenzae. The organization of the genes in the region showed no resemblance to that in the corresponding regions of other bacteria sequenced so far. The gyrA gene was mapped 35 kb downstream from the gyrB gene.